Role of hyaluronic acid in the treatment of peri-implant diseases: results of a meta-analysis - López-Valverde, Nansi; López-Valverde, Antonio; Blanco Rueda, José Antonio (Frontiers in Oral Health, 2025)
Peri-implantitis is an infectious-inflammatory disease that affects the tissues surrounding implants and is one of the main causes of implant failure. Hyaluronic acid (HA) is a natural polymer with multiple biomedical and cosmetic applications. The aim of this systematic review and meta-analysis was to evaluate its efficacy in the treatment of peri-implant disease.MethodsIn accordance with PRISMA, the question was established: is HA treatment effective as a sole or adjunctive therapy for the treatment of peri-implantitis? PubMed/Medline, Embase, Cochrane Central, Dentistry & Oral Sciences Source and Web of Science were searched until December 2024. Inclusion criteria were interventional studies (RCTs and case series), according to the PICOs strategy in subjects with peri-implant pathology (participants), treated with HA (intervention) compared to conventionally treated or untreated patients (control) and assessing response to treatment (outcomes).ResultsThirty-two studies were obtained and four were selected. Risk of bias was assessed using the Cochrane Risk of Bias tool and methodological quality using the Joanna Briggs Institute tool. Meta-analysis of parameters was performed for pooled studies and for subgroups. The overall effect was in favour of the experimental group.ConclusionsThe use of HA as background or adjunctive therapy in peri-implantitis may be effective, although well-designed RCTs are warranted to validate the efficacy of the product.Systematic Review RegistrationIdentifier (INPLANSY 2024100050).